Adiponectin and Its Globular Fragment Differentially Modulate the Oxidative Burst of Primary Human Phagocytes - Chedid, Pia; Hurtado-Nedelec, Margarita; Marion-Gaber, Benoit; Bournier, Odile; Hayem, Gilles; Gougerot-Pocidalo, Marie-Anne; Frystyk, Jan; Flyvbjerg, Alan; El Benna, Jamel; Marie, Jean-Claude (The American journal of pathology, 2012)
Adiponectin (Acrp30) belongs to the family of C1q/tumor necrosis factor α (TNFα)-related proteins. Acrp30 circulates as multimers of high, middle, and low molecular weight. In this study, we detected Acrp30 and its globular fragment (gAcrp30) in synovial fluid from rheumatoid arthritis patients. Intriguingly, the LMW form was more abundant in synovial fluid than in serum from both rheumatoid arthritis patients and healthy subjects. We also investigated the effects of Acrp30 and gAcrp30 on reactive oxygen species (ROS) production via the phagocytic NADPH oxidase. Acrp30 inhibited fMLF-induced ROS production by human phagocytes, whereas gAcrp30 enhanced it. gAcrp30's effect is additive with TNFα, whereas Acrp30 inhibited TNFα-induced priming. gAcrp30 enhanced NOX-2 expression at the plasma membrane, with a concomitant increase in p47 phox phosphorylation. Selective inhibitors of p38 mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase 1 (ERK1)/2 abrogated p47 phox phosphorylation by gAcrp30. In contrast, p47 phox phosphorylation was inhibited by Acrp30 in association with increased AMP-activated protein kinase (AMPK) phosphorylation in phagocytes. These results suggest that human phagocyte ROS production is regulated by different mechanisms selective for Acrp30 versus gAcrp30. An imbalance between gAcrp30 and higher molecular weight isoforms of Acrp30 might contribute to chronic inflammation by regulating NADPH oxidase.